Anthelmintic Activity of the Seeds of Carum copticum - CHOUDHARY, G.P. (Asian Journal of Chemistry, 2010)
The ethanolic extract of the seeds of Carum copticum was evaluated for its anthelmintic efficacy in vitro. Graded doses of the extract (10, 50, 100, 200 μg/mL) showed significant anthelmintic activity, with their sensitivity when compared with the standard.